2003
DOI: 10.1080/15428110308984793
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Synthetic Vitreous Fiber Surface Contamination in Office Buildings

Abstract: A reliable method for determining the distribution of synthetic vitreous fiber (SVF) densities found on building surfaces is presented with data collected from rooms in 40 office buildings in the United States. The initial survey of 20 buildings-complete with collection, counting, and analysis of SVF loading-found that nearly 60% of the samples had zero or one fiber counted. To resolve the nondetects, especially for lighter dust loading, the counting technique was modified. The detection limit improved as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
3
1
0
Order By: Relevance
“…The most likely explanation is that fibers from 0.5 to 1 µm in width, present in all filter cassette samples analyzed by SEM (Figure 3 and Figure 4), may remain undetected by PM from the gel tapes. Similar results have previously been presented by Vallarino et al [25], who were unable to detect fibers smaller than 0.85 µm in diameter from gel tapes by PM. There was a statistically significant correlation between the methods ( p < 0.05; R 2 = 0.70), with the filter cassette method (y) yielding results, on average, 63% higher than the gel tape method (x) in a concentration interval from 0.05 to 20 fibers/cm 2 (y = 1.96 + 0.83 fibers/cm 2 ; see Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…The most likely explanation is that fibers from 0.5 to 1 µm in width, present in all filter cassette samples analyzed by SEM (Figure 3 and Figure 4), may remain undetected by PM from the gel tapes. Similar results have previously been presented by Vallarino et al [25], who were unable to detect fibers smaller than 0.85 µm in diameter from gel tapes by PM. There was a statistically significant correlation between the methods ( p < 0.05; R 2 = 0.70), with the filter cassette method (y) yielding results, on average, 63% higher than the gel tape method (x) in a concentration interval from 0.05 to 20 fibers/cm 2 (y = 1.96 + 0.83 fibers/cm 2 ; see Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…In alignment with previous literature, our review suggests that the frequency of cleaning and contact influences MMVF surface density ( Schneider, 1986 ; Vallarino et al, 2003 ). ATSDR relied upon Vallarino et al (2003) to conclude that only low levels of MMVF are expected to be present on common surfaces that are frequently contacted and cleaned ( ATSDR, 2004 ).…”
Section: Discussionsupporting
confidence: 87%
“…In alignment with previous literature, our review suggests that the frequency of cleaning and contact influences MMVF surface density ( Schneider, 1986 ; Vallarino et al, 2003 ). ATSDR relied upon Vallarino et al (2003) to conclude that only low levels of MMVF are expected to be present on common surfaces that are frequently contacted and cleaned ( ATSDR, 2004 ). We observed a positive correlation between air and surface concentrations of MMVF in areas that were seldom cleaned, among studies that assessed both surface and air concentrations of MMVF, suggesting that surface MMVF measurements may provide insight into overall IEQ in seldom cleaned spaces.…”
Section: Discussionsupporting
confidence: 87%
“…Sound and heat insulations of ventilation equipment and acoustic ceiling boards are possible sources of fibers. It has been suggested that MMVFs may be responsible for itchy skin and irritation of the upper respiratory tract and eyes, as well as for outbreaks of 'office eye syndrome' and 'collective dermatitis' [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%